Investing in times of inflation fears: Diversification properties of investments in liquid real assets - Michael B. Grelck; Stefan Prigge; Lars Tegtmeier; Mihail Topalov; Igor Torpan (Hamburg School of Business Administration (HSBA), 2010)
The financial crisis and the rescue measures taken by governments and central banks increased investors' interest in liquidity and in real assets supposed to offer a hedge against inflation. Against this background, we investigate empirically four real assets (real estate, commodities, infrastructure, and shipping) for which there are investment instruments available which trade in liquid markets. Our empirical study using data from 1999 to 2009 yields several results: First, in most cases, the addition of real assets improved portfolio performance (measured with Sharpe ratio, Sortino ratio, Omega ratio, and Modified Sharpe ratio) in comparison with a base portfolio consisting only of standard stocks and bonds. Among the four real assets, infrastructure and shipping clearly outperformed commodities and real estate. Second, the time frame chosen for the analysis matters very much. This is bad news for investors because there is no such thing as the single 'true' time frame for this purpose. Due to our analytical approach, we regard our conclusions, in spite of their general time dependence, as rather solid. Third, despite great conceptual differences, our four performance measures lead to the same conclusions. This result is interesting for investors beyond our specific setting because the selection of a specific performance measure from the vast supply of such measures does not seem to matter much.
Keywords: G11; G15; 650; diversification; inflation; portfolio choice; investments in real assets